Light Trapping: Light Trapping in Ultrathin Monocrystalline Silicon Solar Cells (Adv. Energy Mater. 11/2013). Issue 11 (November 2013) - Yu, Ki Jun; Gao, Li; Park, Jae Suk; Lee, Yu Ri; Corcoran, Christopher J.; Nuzzo, Ralph G.; Chanda, Debashis; Rogers, John A.
<x xml:space="preserve">Abstract</x> On page 1401, Debashis Chanda, John A. Rogers, and co‐workers report ultrathin (3 μm) singlecrystalline silicon solar cells with electromagnetically optimized light‐trapping schemes that offer greatly enhanced absorption and corresponding improvements in efficiency of cell performance. Optically optimized cells of this type yield energy conversion efficiencies that are ≈190% higher compared to otherwise identical cells that do not exploit light trapping features, and an efficiency of 8.5% is recorded in this ultrathin film geometry <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>